2013
DOI: 10.1097/jcp.0b013e3182984015
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Delta9-Tetrahydrocannabinol Influences Circulating Endogenous Cannabinoids in Humans

Abstract: Delta⁹-tetrahydrocannabinol (THC) competes with the endogenous cannabinoids arachidonoyl ethanolamide (anandamide) and 2-arachidonoyl glycerol (2-AG) at cannabinoid receptors. This may cause adaptive changes in the endocannabinoid signaling cascade with possible consequences for the biological functions of the endocannabinoid system. We show that administration of a single oral dose of 20 mg THC to 30 healthy volunteers resulted in higher circulating concentrations of anandamide, 2-AG, palmitoyl ethanolamide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
3
23
1
Order By: Relevance
“…effect was corroborated in a second experiment in rats with the synthetic cannabinoid WIN-55,212 (Walter et al, 2013). However, the fact that the present study examined induced gamma oscillations at a mean of 42.9 h after last cannabis exposure makes this mechanism unlikely.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…effect was corroborated in a second experiment in rats with the synthetic cannabinoid WIN-55,212 (Walter et al, 2013). However, the fact that the present study examined induced gamma oscillations at a mean of 42.9 h after last cannabis exposure makes this mechanism unlikely.…”
Section: Discussionsupporting
confidence: 56%
“…First, as THC competes with endocannabinoid transmitters at the CB1R, recent cannabis exposure may cause a compensatory increase in the synthesis and release of endocannabinoids such as anandamide and 2-arachidonoyl glycerol (2-AG). Indeed, a recent study in humans demonstrated that a single oral dose of 20 mg THC resulted in significant increases in anandamide, 2-AG, palmitoyl ethanolamide, and oleoylethanolamide for several hours after administration (Walter et al, 2013). This Figure 2 Grand-averaged time  frequency plots demonstrating mean trial power (MTP) for midline electrodes during the incoherent motion condition for the healthy control and cannabis groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that CBD alleviates the psychotic symptoms of schizophrenia, possibly in part by elevating levels of AEA and N-acylethanolamines in humans (17). Another report showed that administration of a single oral dose of 20 mg of THC to 30 healthy volunteers resulted in higher circulating concentrations of anandamide, 2-AG, palmitoyl ethanolamide, and oleoylethanolamide (61). Therefore, it is tempting to speculate that phytocannabinoids modulate the endocannabinoid tone by targeting FABPs in humans (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements took place before (baseline) and 2 h post medication (THC or placebo) when maximum pharmacological effects were expected (Hollister et al, 1981). During measurements after THC administration, plasma concentrations of THC and its metabolites THC-OH and THC-COOH were 6.4 ± 3.9 ng/ml, 6 ± 3.2 ng/ml, and 43.3 ± 20.2 ng/ml (mean ± standard deviation), respectively (for further details, see Walter et al, 2013).…”
Section: Subjects Study Design and Medicationsmentioning
confidence: 99%